A gendered analysis of household energy consumption behavior a comparative study. - Babael, Diana Martinelli C.; Riel, Veronica A.; Yodico, Elaisa Trisha M. (Diana Martinelli C. Babael, Veronica A. Riel, and Elaisa Trisha M. Yodico, 2019)
High levels of energy consumption can result to the exhaustion of fossil energy reserves available in a country, which poses a threat to energy supply. In the Philippines, household consumption accounts for a significant percentage of national energy consumption. For these reasons, the study sought to describe and analyze energy consumption. For these reasons, the study sought to describe and analyze energy consumption behavior at the household level, primarily looking into the effects of gender on energy use and consumption. The attention placed on the gender dimension of energy consumption arose from the lack of sex-aggregated data on domestic energy-related attitudes and practices. The study mainly sought to identify differences between men and women's energy consumption behavior at the household level.